دور مشروعات ريادة الاعمال في تحقيق التنمية المستدامة: دراسة ميدانية على منطقة عسير (Journal of Economics and Management Research, 2022)
تعتبر ريادة الأعمال من الحقول الهامة في اقتصاديات الدول المتقدمة والنامية على حد سواء، وتأتي هذه الأهمية للدور الكبير لريادة الأعمال في تجديد النسيج الاقتصادي، دعم الابتكار والبحث عن الفرص. وتهدف هذه الدراسة الى معرفة دور مشاريع ريادة الأعمال في تحقيق التنمية المستدامة في المملكة العربية السعودية، واظهرت الدراسة عدة نتائج منها فقد بينت الدراسة أن السلوك الريادي لرواد ورائدات الأعمال يساهم بدرجة فعالة في تحقيق مشاريع التنمية المستدامة في كافة القطاعات. Entrepreneurship is considered one of the important fields in the economies of developed and developing countries alike, and this importance comes from the great role of entrepreneurship in renewing the economic fabric, supporting innovation and searching for opportunities. This study aims to know the role of entrepreneurship projects in achieving sustainable development in the Kingdom of Saudi Arabia, and the study showed several results, including the study showed that the entrepreneurial behavior of male and female entrepreneurs effectively contributes to achieving sustainable development projects in all sectors.